Structure and Tribotechnical Properties of Al-Sn Alloys Prepared by the Method of Liquid-Phase Sintering; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Rusin N. M. (Advanced Materials and Nanotechnology, 2014)
Title screen